2012
DOI: 10.1002/jemt.22116
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization, gene expression, and enzymatic activity of cyclooxygenases, prostaglandin e2‐9‐ketoreductase, and nitric oxide synthases in mediterranean buffalo (bubalus bubalis) corpora lutea during diestrus

Abstract: Immunopresence, gene expression, and enzymatic activity of cyclooxygenase 1 (COX1), COX2, PGE2-9-ketoreductase (PGE2-9-K), endothelial (eNOS), and inducible nitric oxide synthases (iNOS), and hormone in vitro production were examined in early, mid, late, and regressive buffalo corpora lutea (CL). COX1 immunosignals were detected in the cytoplasm of small luteal cells, COX2 in large luteal cells, and PGE2-9-K in all luteal cells. COX2 and PGE2-9-K immunosignals were greater in late CL. Immunopresence of both NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
0
16
2
Order By: Relevance
“…2). In previous studies on buffalo CL [10,11], it was shown that PTGS1 enzymatic activity was higher in late stage and lower in regressive CL, while PTGS2 increased from early to late CL and, differently from the present data, became higher in regressive CL. It is interesting to note that regressive CL is accompanied by general decline (p < 0.01) of PTGS and NOS enzymatic activities (Fig.…”
Section: Resultscontrasting
confidence: 90%
See 2 more Smart Citations
“…2). In previous studies on buffalo CL [10,11], it was shown that PTGS1 enzymatic activity was higher in late stage and lower in regressive CL, while PTGS2 increased from early to late CL and, differently from the present data, became higher in regressive CL. It is interesting to note that regressive CL is accompanied by general decline (p < 0.01) of PTGS and NOS enzymatic activities (Fig.…”
Section: Resultscontrasting
confidence: 90%
“…CLs were separated by blunt dissection from the surrounding ovarian tissues and classified into four groups, covering the entire cycle length, as described previously [1,3]: early (Days 4-6), mid (8)(9)(10)(11)(12), late (14)(15)(16), and regressive (19)(20)(21). CLs were cut in half longitudinally for the following immunohistochemical investigation and enzymatic activity assays.…”
Section: Animals and Tissue Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…All the animals did not present reproductive abnormalities. The specimens were immediately fixed and processed for lectin histochemistry using procedures previously described (Parillo & Diverio 2009b;Parillo et al 2012Parillo et al , 2013Zerani et al 2012, in press). The sections were dipped in 0.3% H 2 O 2 /methanol for 1 hour to inhibit endogenous peroxidase activity, washed with PBS, then incubated in a moist chamber for 1 hour at room temperature with a solution of horseradish peroxidase (HRP) conjugated lectins (Sigma-Aldrich, St Louis, MO, USA) in 0.1 M PBS, pH 7.2, containing 0.1 mM CaCl 2 , MgCl 2 and MnCl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The slides were incubated with the following primary rabbit polyclonal antibodies (Abcam, Cambridge): anti-nNOS (1:250), anti-eNOS (1:10) and anti-iNOS (1:200) [15,17]. Then, the slides were incubated with biotinylated goat antirabbit secondary antibody (Santa Cruz Biotechnology, CA, USA), exposed to avidin-biotin complex (ABC kit, Vector Laboratories) and the peroxidase activity sites were visualised using the DAB kit (Vector Laboratories) as chromogen [4,20].…”
Section: Immunohistochemistry Of Nnos Enos and Inosmentioning
confidence: 99%